Pengaruh Sistem Pengukuran Kinerja dan Sistem Reward terhadap Total Quality Management dan Kinerja Managerial pada Mic Transformer Surabaya - Pujianto, Wahyu Eko (JKMP (Jurnal Kebijakan dan Manajemen Publik), 2013)
This causative research is aimed to present the influence of any system of performance measurement and rewards system towards the implementation of total quality measurement and managerial performance on the mics of transformers in Surabaya. The population of the research was all 56 employees of the MIC transformers, and the technique used total sampling. The technique of collecting data is done by the spread of questionairre. The technique of analysis was linear regression by using f test and t test to test the hypothesis. The results indicated that system of performance measurement and rewards system has an influence toward the implementation of TQM and managerial performance. It showed that the better system of measurement on the performance of employees and the rewards system applied by a company would increase TQM and managerial performance produced by the company. The greater attention to the needs of company employees, the more productivity the company will get.